2020
DOI: 10.2339/politeknik.591100
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de Ömrünü Tamamlamış Lastiklerin Yönetiminde En Uygun Bertaraf Seçeneğinin PROMETHEE Ve Bulanık PROMETHEE Yöntemi ile Belirlenmesi

Abstract: Sürdürülebilir bir atık yönetim yaklaşımının ekonomik, sosyal ve çevresel unsurların tümüne hizmet edebilmesi gerekir. Bu çalışmada atık lastiklerin yönetiminde direkt geri dönüşüm, piroliz ve alternatif yakıt olarak değerlendirme alternatifleri değerlendirilmiştir. Sayılan bu alternatif metotlardan Türkiye için en uygun yöntem, çok kriterli karar verme süreci olan PROMETHEE (preference ranking organization method for enrichment evaluations) ve bulanık PROMETHEE yöntemi ile belirlenmiştir. En uygun alternatifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
4
0
4
Order By: Relevance
“…For ELTs management, disposal options vary according to the purpose of use and cost, and are generally grouped into four groups: recycling, reuse, storage, and energy/material recovery. It has been reported that the most suitable alternative in Turkey is recycling, and only the cost of installation criterion has a negative effect on the preferability of this alternative [10]. Rubber modified bitumen is defined as a material that can be used in bituminous layers that are aimed suitable for purposes such as reducing noise and increasing the coating performance in the Turkey Highway Technical Specification, Section-418.…”
Section: Introductionmentioning
confidence: 99%
“…For ELTs management, disposal options vary according to the purpose of use and cost, and are generally grouped into four groups: recycling, reuse, storage, and energy/material recovery. It has been reported that the most suitable alternative in Turkey is recycling, and only the cost of installation criterion has a negative effect on the preferability of this alternative [10]. Rubber modified bitumen is defined as a material that can be used in bituminous layers that are aimed suitable for purposes such as reducing noise and increasing the coating performance in the Turkey Highway Technical Specification, Section-418.…”
Section: Introductionmentioning
confidence: 99%
“…Bu sebeple, atık lastiklerin geri dönüştürülerek tekrar kullanımı konusu ciddi önem arz etmektedir. Araştırmacılar, yapı olarak oldukça dayanıklı olan bu malzemeleri çoğunlukla piroliz işlemine tabi tutarak geri dönüşüme kazandırmaya çalışmışlardır [16,17]. Piroliz işlemi, organik maddelerin oksijensiz ortamda 500-800 o C'de gaz, sıvı veya katı ürünlere dönüştürülmesi prosesi olarak tanımlanmaktadır.…”
Section: Introductionunclassified
“…Piroliz işlemi, organik maddelerin oksijensiz ortamda 500-800 o C'de gaz, sıvı veya katı ürünlere dönüştürülmesi prosesi olarak tanımlanmaktadır. Atık lastiklerin piroliz işlemine tabi tutulmasıyla pirolitik yağlar, siyah karbon (karbon siyahı), çelik tel ve yanıcı gazlar elde edilmektedir [15,17]. Elde edilen bu malzemelerden pirolitik yağlar, mazot eş değeri bir malzeme olup yakıt olarak kullanılırken, çelik tel haddehanelere satılan ve az da olsa değer elde edilen bir üründür.…”
Section: Introductionunclassified
See 2 more Smart Citations